Nitrogen differentially modulates photosynthesis, carbon allocation and yield related traits in two contrasting Capsicum chinense cultivars - de Ávila Silva, Lucas (Plant science : an international journal of experimental plant biology, 2019)
Copyright © 2019 Elsevier B.V. All rights reserved.